Premature Graying of Hair: A Comprehensive Review and Recent Insights - Kavita Poonia; Mala Bhalla (Wolters Kluwer Medknow Publications, 2024)
Background: Hair symbolizes well-being and self-expression, with graying occurring naturally among different racial groups at varying ages. Premature graying has psychological and societal impacts, influencing self-esteem and quality of life. Gray hair usually advances gradually and is permanent, with occasional reports of natural repigmentation. Premature graying of hair (PMGH) results from a complex interplay of genetic, environmental, and cellular factors. Materials and Methods: Studies exploring links between gray hair and conditions such as osteopenia, hearing loss, smoking, obesity, dyslipidemia, and cardiovascular disease have yielded mixed results. Despite continuous research into the causes of gray hair, effective, evidence-based treatments are lacking and still need to be improved. Conclusion: Herein, we reviewed the causes, mechanisms, risk factors, psychosocial effects, and emerging therapies for PMGH.